A reference grammar of Russian - Timberlake, Alan (Cambridge University, 2013)
A Reference Grammar of Russian describes and systematizes all aspects of the grammar of Russian: the patterns of orthography, sounds, inflection, syntax, tense-aspect-mood, word order, and intonation. It also refers to literature on variation and trends in the development of Russian, and makes use of contemporary data from the internet.